Ex Vivo Assessment of Different Oral Anticoagulant Regimens on Pump Thrombosis in a HeartWare Ventricular Assist Device. (July 2021) - Rao, Sriram D.; Connor, David E.; Shehab, Sajad; Kerr, Nicholas P.; Joseph, Joanne; Muthiah, Kavitha; Jain, Pankaj; Robson, Desiree; Jansz, Paul; Hayward, Christopher S.
Abstract : Background: In light of decreased intracranial hemorrhage with direct oral anticoagulants and concerns about their safety in continuous flow left ventricular assist devices, we conducted an ex vivo study of thrombus formation using multiple anticoagulation agents. Methods: A continuous flow left ventricular assist device (HeartWare ventricular assist device) hemocompatibility loop was run using human blood under 7 conditions: control (no anticoagulation or antiplatelet); in vitro addition of aspirin; in vitro addition of apixaban at low dose (equivalent 2.5 mg twice daily); addition of apixaban at high dose (equivalent 5 mg twice daily); patients on warfarin; patients on apixaban (5 mg twice daily); and patients on dabigatran (150 mg twice daily). The primary outcome was time to formation of intrapump thrombosis. Secondary outcomes were reduction in clotting times over 1 hour, hemolysis, reduced platelet aggregation, and von Willebrand activity. Results: Twenty-one runs were completed. Times to thrombosis in median (interquartile range) were control, 131 (127–134.5); in vitro aspirin, 124 (114.5–137); and patients on dabigatran, 131 (130.5–135.5) minutes, respectively. Times in patients on warfarin were, 137 (136.5–143.5); in vitro low-dose apixaban, 141 (138.5–142); and patients on apixaban, 140 (138–142.5) minutes, respectively. No thrombus formed in the in vitro high-dose apixaban group. There were no significant differences between the individual groups. When all apixaban groups were compared with nonapixaban groups, the time to thrombosis formation was significantly longer, 143 (137–150) versus 133.5 (128.5–140) minutes, P =0.02. There were similar changes in lactate dehydrogenase levels and other secondary end points. Conclusions: In an in vitro study of anticoagulation using human blood in a mock loop with a HeartWare HVAD, we demonstrated similar thrombosis times for apixaban and warfarin. Time to clotting was longer in the combined apixaban groups compared with combined other groups, but thrombosis times between individual groups were not significantly different.